Replacement of doped Olympic medalists - Geistlinger, M.; Bachl, N.; Pigozzi, F.; Pitsiladis, Y. (Current Sports Medicine Reports, 2017)
A summary of the outcomes of the International Olympic Committee (IOC) retesting program from 2008 to 2012 to date was recently released (6). Key outcomes include 104 offenses, of which 86 cases were related to the territory of the former Soviet Union. Russia lost 19 medals, Kazakhstan 9, Belarus 6, the Ukraine 5, Armenia and Moldova 2 each, Azerbaijan and Uzbekistan 1 each. China lost three medals, Turkey, two medals; Cuba and Greece, one medal. Five athletes tested positive for both the 2008 and 2012 Olympic Games (7). However, it remains to be determined who has received or will receive these medals. This uncertainty is due to the fact that the responsibility for changing the results lies with the respective international federation (IF) and the responsibility for redistributing the medals lies with the IOC. The most common scenario is that the next-placed athlete is moved up, although this can cause difficulties and there are precedents not to award these medals. In the 94 kg men's weightlifting competition in the 2012 London Olympic Games, the 5th, 8th, and 9th ranked athletes, theoretically at least, remain in contention for the medal positions (5). With the present system, it is difficult to determine whether all of these potentially ''eligible'' athletes have undergone dopingcontrol. The International Weightlifting Federation (IWF) has published on its Web site a list of all male competitors and another of all female competitors who underwent doping control in the 2012 Olympic Games and these data reveal the originally ninth and now third position athlete was subject to doping control at the 2012 Olympic Games (2). Nevertheless, there is the theoretical possibility that the redistribution of Olympic medals could lead to nontested athletes becoming holders of medals.